PENGARUH PENGGUNAAN AMPAS TAHU TERFERMENTASI KHAMIR Saccharomyces spp DALAM RANSUM TERHADAP DISTRIBUSI LEMAK DAN KOLESTEROL DARAH BROILER - N. G. P. S, Kirana; Bidura, I G. N. G.; Puspani, E. (Jurnal Peternakan Tropika, 2017)
The purpose this research is to know the effect of use 20% tofu waste fermented by  Saccharomyces spp in ration on fat distribution and cholesterol serum of broiler. The experiment used of Complete RandomizedDesign (CRD) with three treatments and six replicates, with three birds in each replicated. The treatments were basal diets as control (A), diets with 20% unfermented tofu waste (B), and diets with 20% tofu waste fermented by Saccharomyces spp (C), respectively. Results of this experiment showed that the fat pad of broiler in treatment C were significantly different (P < 0.05) lowerboth than treatment A and B. Total cholesterol serum of broiler in treatment C was lower significantly (P < 0.05) than treatment A, but not significant with treatment B. Mesenteric fat and  ventriculus fat real has no effect in all treatments.  It can be concluded that used of 20% tofu waste fermented by Saccharomyces spp in the ration can lower the percentage of pad fat and total cholesterol serum of broiler; and used of 20% tofu waste unfermented can be decrease total cholesterol serum of broiler.
Keywords: tofu waste, Saccharomyces spp, body fat, cholesterol, broiler